(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The main function of the suspension system and its components is to absorb vibrations when the vehicle moves over bumps and to provide its stability in the different operating modes. Some of the vibration parameters are natural frequencies and mode shapes. This paper presents the results of the natural frequencies of an arm of the MacPherson front independent suspension using different bushings. For this purpose, three-dimensional geometric model of the arm was created and its frequency analysis was performed by Finite Element Analysis (FEA) using SolidWorks software. The obtained results of the natural frequencies of the arm with different bushings by FEA were presented and compared with those obtained experimentally.